System-Wide Impacts of Hospital Payment Reforms: Evidence from Central and Eastern Europe and Central Asia - Moreno-Serra, Rodrigo; Wagstaff, Adam (2012)
While there is broad agreement that the way that health care providers are paid affects their performance, the empirical literature on the impacts of provider payment reforms is surprisingly thin. During the 1990s and early 2000s, many European and Central Asian (ECA) countries shifted from paying hospitals through historical budgets to fee-for-service (FFS) or patient-based payment (PBP) methods (mostly variants of diagnosis-related groups, or DRGs). Using panel data on 28 countries over the period 1990-2004, we exploit the phased shift from historical budgets to explore aggregate impacts on hospital throughput, national health spending, and mortality from causes amenable to medical care. We use a regression version of difference-in-differences (DID) and two variants that relax the DID parallel trends assumption. We find that FFS and PBP both increased national health spending, including private (i.e. out-of-pocket) spending. However, they had different effects on inpatient admissions (FFS increased them; PBP had no effect), and average length of stay (FFS had no effect; PBP reduced it). Of the two methods, only PBP appears to have had any beneficial effect on "amenable mortality", but we found significant impacts for only a couple of causes of death, and not in all model specifications.